Principio de conservación de la energía - J. Gambi; A. Frascino (Revista de Enseñanza de la Física, 2016)
This report describes a low cost teaching equipment designed for the experimental verificatian of the conservation of Energy by High School students. It includes a brief otuline of the theory of the experiment, description of experimental procedures, an analysis of results and drawings and instructions so as to allow the reproduction fo the apparatus.